Data Mining Techniques in a Virtual Workshop for the Digitalization of Education - E. V. Timoschenko; A. F. Razhkov (Цифровая трансформация)
A software module has been developed that forms the basis of a virtual laboratory workshop and consists of two computer applications that use the methods of intelligent analysis of biomedical data for an example of the possibility of predicting a disease based on the proposed symptoms of a patient and determining the likelihood of cardiovascular disease. The developed virtual laboratory practice can be used in teaching the block of biomedical disciplines and includes a list of laboratory works that help to acquire practical skills in bioanalytical work and programming skills in Python.